Pengaruh Ketaatan Aturan Akuntansi, Pengendalian Internal Dan Kecerdasan Spiritual Terhadap Kecenderungan Kecurangan - Ni Made Ayu Meri Yani; Ni Komang Sumadi; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2022)
Fraud is a form of rule violation that has a detrimental effect on many people. Many factors underlie a fraud occurs. This study aims to see how much compliance with accounting rules, internal control, and spiritual intelligence can affect the level of a person's tendency to commit fraud in an institution. The LPD of Melaya Regency was used as the research location with all of its employees being the research population. This study uses 45 people as a sample which will later be distributed questionnaires to obtain data and studied by setting the use of multiple linear regression analysis. The view of this study found that the tendency of fraud can be reduced if the institution has high compliance with accounting rules, strict internal control, and good spiritual condition.